Biological treatment in ankylosing spondylitis in the Nordic countries during 2010–2016: a collaboration between five biological registries. (2nd November 2018) - Glintborg, B; Lindström, U; Aaltonen, K; Kristianslund, EK; Gudbjornsson, B; Chatzidionysiou, K; Askling, J; Nordström, D; Hetland, ML; Di Giuseppe, D; Dreyer, L; Kristensen, LE; et al.
Abstract : Objectives : Large-scale observational cohorts may be used to study the effectiveness and rare side effects of biological disease-modifying anti-rheumatic drugs (bDMARDs) in ankylosing spondylitis (AS), but may be hampered by differences in baseline characteristics and disease activity across countries. We aimed to explore the research infrastructure in the five Nordic countries regarding bDMARD treatment in AS. Method : This observational cohort study was based on data from biological registries in Denmark (DANBIO), Sweden (SRQ/ARTIS), Finland (ROB-FIN), Norway (NOR-DMARD), and Iceland (ICEBIO). Data were collected for the years 2010–2016. Registry coverage, registry inventory (patient characteristics, disease activity measures), and national guidelines for bDMARD prescription in AS were described per country. Incident (first line) and prevalent bDMARD use per capita, country, and year were calculated. In AS patients who started first line bDMARDs during 2010–2016 (n = 4392), baseline characteristics and disease activity measures were retrieved. Results : Registry coverage of bDMARD-treated patients ranged from 60% to 95%. All registries included extensive prospectively collected data at patient level. Guidelines regarding choice of first line drug and prescription patterns varied across countries. During the period 2010–2016 prevalent bDMARD use increased (p < 0.001), whereas incident use tended to decrease (p for trend < 0.004), with large national variations (e.g. 2016 incidence: Iceland 10.7/100 000, Finland 1.7/100 000). Baseline characteristics were similar regarding C-reactive protein, but differed for other variables, including the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) (range 3.5–6.3) and Ankylosing Spondylitis Disease Activity Score (ASDAS) (2.7–3.8) (both p < 0.0001). Conclusion : Collaboration across the five Nordic biological registries regarding bDMARD use in AS is feasible but national differences in coverage, prescription patterns, and patient characteristics must be taken into account depending on the scientific question.